Panchromatic Absorption and Oxidation of an Iron(II) Spin Crossover Complex - Moll, Johannes; Foerster, Christoph; Koenig, Alexandra; Carrella, Luca M.; Wagner, Manfred; Panthoefer, Martin; Moeller, Angela; Rentschler, Eva; Heinze, Katja (Inorganic Chemistry, 2022)
In order to expand and exploit the useful properties of d6-iron(II) and d5-iron(III) complexes in potential magnetic, photophysical, or magnetooptical applications, crucial ligand-controlled parameters are the ligand field strength in a given coordination mode and the availability of suitable metal and ligand frontier orbitals for charge-transfer processes. The push-pull ligand 2,6-diguanidylpyridine (dgpy) features low-energy π∗ orbitals at the pyridine site and strongly electron-donating guanidinyl donors combined with the ability to form six-membered chelate rings for optimal metal-ligand orbital overlap. The electronic ground states of the pseudo-octahedral d6- and d5-complexes mer-[Fe(dgpy)2]2+, cis-fac-[Fe(dgpy)2]2+, and mer-[Fe(dgpy)2]3+ as well as their charge-transfer (CT) and metal-centered (MC) excited states are probed by variable temperature UV/vis absorption, NMR, EPR, and Mössbauer spectroscopy, magnetic susceptibility measurements at variable temperature as well as quantum chemical calculations.
CRIS-Team Scopus Importer:2023-03-27